Driving Performance in Adventure Tourism: The Impact of Transformational Leadership, Organizational Climate, And Individual Characteristics in A Leading Bali Enterprise - Ni Made Rika Monika; I Nengah Suardhika; I Gede Rihayana (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Royal Bali Adventure Bongkasa is a nature-based tourism service company that serves domestic and foreign tourists. The company is required to have qualified employees in order to provide optimal service. However, employee performance has not been optimal due to the influence of transformational leadership, organizational climate, and individual characteristics that have not been fully optimized. This study used a quantitative method with saturated sampling technique, where all 36 employees were sampled. Data collection was conducted through observation, interviews, documentation, and questionnaires. Data analysis used multiple linear regression with the help of the SPSS program. The results of this study indicate that (1) transformational leadership has a positive and significant effect on employee performance at Royal Bali Adventure Bongkasa, which means that if leadership is good, performance will also increase, (2) organizational climate has a positive and significant effect on employee performance at Royal Bali Adventure Bongkasa, which means that the better the organizational climate, the higher the employee performance, (3) individual characteristics have a positive and significant effect on employee performance at Royal Bali Adventure Bongkasa, which means that the better the individual characteristics of an employee, the higher the employee performance shown.